2020
DOI: 10.1111/are.14567
|View full text |Cite
|
Sign up to set email alerts
|

Assessing peracetic acid for controlling post‐vaccination Saprolegnia spp.‐associated mortality in juvenile Atlantic salmon Salmo salar in freshwater recirculation aquaculture systems

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, use of some of these chemicals is either limited or banned due to several undesirable effects such as toxic and carcinogenic properties (Bly et al., 1996), causing the egg's cell wall to be vulnerable to entrance of other pathogens (Branson, 2002; Kirsty et al., 2014; Oono et al., 2008), and the adverse consequences of the repetitive and in high‐dose application on the environment (Bailey, 1984; Bailey & Jeffrey, 1989; Dentler, 1982; Marking et al., 1994; Schreck et al., 1991). Moreover, it has been found that some chemicals that have the competence to effectively eliminate or control the fungus such as permanganate (Sherif & Abdel‐Hakim, 2016), chlorine dioxide, chitosan and copper fibre (Emara et al., 2020) have negative effects on the survival rate of the eggs or juveniles (Good et al., 2020). Therefore, natural therapeutic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of some of these chemicals is either limited or banned due to several undesirable effects such as toxic and carcinogenic properties (Bly et al., 1996), causing the egg's cell wall to be vulnerable to entrance of other pathogens (Branson, 2002; Kirsty et al., 2014; Oono et al., 2008), and the adverse consequences of the repetitive and in high‐dose application on the environment (Bailey, 1984; Bailey & Jeffrey, 1989; Dentler, 1982; Marking et al., 1994; Schreck et al., 1991). Moreover, it has been found that some chemicals that have the competence to effectively eliminate or control the fungus such as permanganate (Sherif & Abdel‐Hakim, 2016), chlorine dioxide, chitosan and copper fibre (Emara et al., 2020) have negative effects on the survival rate of the eggs or juveniles (Good et al., 2020). Therefore, natural therapeutic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we were limited to conducting research in a flow‐through system; however, previous on‐site research has demonstrated no impact on fluidized sand biofiltration when RAS were exposed to low‐dose (up to 0.3 mg/L) PAA on a semi‐continuous basis (Davidson et al, 2019). A further study demonstrated that TAN removal efficiency was not impacted when fluidized sand biofilters were exposed to a daily pulse dose of 0.2 mg/L, 0.5 mg/L or 1.0 mg/L PAA, and that these treatments decreased saprolegniasis following intracoelomic injection vaccination (Good et al, 2020). In comparison, concentrations of 2–3 mg/L PAA can disrupt biofilter nitrification, leading to increases in nitrite levels in RAS (Pedersen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The development of disinfection strategies to control pathogen outbreaks in the culture water and water treatment units in RASs without negatively affecting fish health and welfare or the nitrifying bacteria community in the biofilters is challenging. Infectious pathogens in fish research facilities are common (Kent et al, 2009), and several disinfection technologies such as ozone (Powell and Scolding, 2018), UV irradiation (Summerfelt et al, 2009b), or chemicals (e.g., peracetic acid (PAA) based products) added to the water (Good et al, 2020) were evaluated to address this issue. It is important to note that majority of the facilities being used to study diseases in Atlantic salmon under controlled conditions use flow-through systems.…”
Section: Introductionmentioning
confidence: 99%